Pengaruh Program Tahfidz Terhadap Prestasi Belajar Siswa di MTs Darussalam Taman Sidoarjo - Cicik Saidatul Qomariyah; Masfufah Masfufah (Jurnal Budi Pekerti Agama Islam, 2024)
The Tahfidz program is an effort that is said to be very successful in shaping children into moral individuals and developing their character. By maintaining memorization in reading according to the norms of tajwid, makharijul letters, fashohah, and tartil. This research is known as correlational research with quantitative methods and data collection tools which include questionnaires, documentation and observation. Descriptive analysis and hypothesis analysis are used in data analysis techniques. This is proven from data analysis using percentage analysis, the Tahfidz program at MTs. Darussalam Taman Sidoarjo which has 91.33% entered at the interval 81%-100%. This shows that the tahfidz program at MTs. Darussalam Taman Sidoarjo has a very high value. Based on product-moment correlation analysis, the tahfidz program at MTs Darussalam does not interfere with student learning achievement. It can be seen that the calculated "r" value = 0.433, when consulted on the interval table, the score coefficient is 0.40 - 0.599, which states that it is moderate, which clearly shows that with the existence of the Tahfidz program at MTs. Darussalam Sidoarjo Park. And this tahfidz program is very necessary to increase student achievement scores.